2023
DOI: 10.1007/s11934-023-01146-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Contemporary Surgical Outcomes Between Holmium Laser Enucleation of the Prostate and Robotic-Assisted Simple Prostatectomy

Abstract: Purpose of ReviewThis study reviews contemporary literature on RASP and HoLEP to evaluate perioperative outcomes, common complications, cost analytics, and future directions of both procedures. Recent Findings RASP is indicated for prostates > 80 mL, while HoLEP is size-independent. No notable differences were found in operative time, PSA nadir (surrogate for enucleation volume), re-catheterization rates, or long-term durability. Prolonged incontinence and bladder neck contracture rates are low for both surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“… 6 Although minimally invasive approaches such as laparoscopic or robotic simple prostatectomy has been advocated for prostates >80 ml, 7 , 8 recent evidence has demonstrated that EEP with HL is as safe and equally effective with shorter hospitalizations, lower transfusion rates, shorter catheterization time, lower costs, and even feasible for same-day discharge. 9 However, most of the published studies include single-center series with the majority of the large prostate volumes ranging between 80–100 ml with even fewer studies report outcomes for prostate volumes of more than 150–200 ml. 5 , 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“… 6 Although minimally invasive approaches such as laparoscopic or robotic simple prostatectomy has been advocated for prostates >80 ml, 7 , 8 recent evidence has demonstrated that EEP with HL is as safe and equally effective with shorter hospitalizations, lower transfusion rates, shorter catheterization time, lower costs, and even feasible for same-day discharge. 9 However, most of the published studies include single-center series with the majority of the large prostate volumes ranging between 80–100 ml with even fewer studies report outcomes for prostate volumes of more than 150–200 ml. 5 , 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…EAU, NICE, and AUA guidelines recommend laser-based EEP for prostates larger than 80 ml a reference standard being currently held for large prostates [ 8 ]. Recently, laparoscopic or robotic simple prostatectomy has been advocated for prostates > 80 cc with pros and cons for each [ 9 ] but even for large prostates HoLEP is as safe and equally effective and offers shorter hospitalizations, lower transfusion rates, shorter catheterization time, lower costs, and even feasible for same-day discharge [ 10 ]. However, most of the published studies included single-center series with the majority of the large prostate volumes ranging between 80 and 100 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Im Vergleich zur RAE fallen bei AEEP niedrigere Personalkosten an, da in der Regel nur ein Operateur und 1-2 Pflegekräfte benötigt werden. Zudem sind die Investitions-und vor allem die Sachkosten deutlich geringer [34]. Somit ist davon auszugehen, dass die AEEP der deutlich kosteneffizientere Eingriff ist.…”
Section: Aktuelle Datenlageunclassified